RETRACTION: An Investigation of Corporate Social Responsibility Conformity: The Roles of Network Prominence and Supply Chain Partners (Journal of Operations Management, 2026)
RETRACTION: E.C. Falcone and J.W. Ridge , “,” Journal of Operations Management 70 , no. ( 2024 ): 600 – 629 , https://doi.org/10.1002/joom.1302 . The above article, published online on 27 March 2024 in Wiley Online Library ( http://onlinelibrary.wiley.com/ ), and its correction ( https://doi.org/10.1002/joom.1350 ), have been retracted by agreement between the journal Editors‐in‐Chief, Elliot Bendoly and Rogelio Oliva; the Association for Supply Chain Management; and Wiley Periodicals LLC. A third party raised concerns with the editors regarding data irregularities throughout the article's text and tables. Following an investigation, the editors noted that the identified transcription errors significantly impacted the article's conclusions, and affected their confidence in the results reported. The authors provided raw data and analysis code for review, which allowed for identification of the transcription and methodological errors. However, the editors determined that the authors’ explanation and data was not sufficient to resolve the concerns, and therefore the article must be retracted.